2015
DOI: 10.1039/c5ee00548e
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-activated graphene-heterostructure transparent cathodes: enabling high-performance n-graphene/p-Si Schottky junction photovoltaics

Abstract: A record-high efficiency (>10%) was achieved for an n-graphene/p-Si Schottky junction solar cell by using the “sunlight-activated” graphene/TiOx transparent cathode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
(42 reference statements)
3
30
0
Order By: Relevance
“…Stability of the device is one of the most common drawbacks, which mainly pertains to the stability of Gr/Si interface. The Gr/Si interface can be easily and continuously oxidized even with Gr on the top, which gradually reduces the tunneling rate of carriers. Theoretically, Gr with perfect lattice is impermeable even to molecules as small as helium .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stability of the device is one of the most common drawbacks, which mainly pertains to the stability of Gr/Si interface. The Gr/Si interface can be easily and continuously oxidized even with Gr on the top, which gradually reduces the tunneling rate of carriers. Theoretically, Gr with perfect lattice is impermeable even to molecules as small as helium .…”
Section: Discussionmentioning
confidence: 99%
“…To stabilize the Gr/Si interface, passivation and protection would be needed. Gr/Si solar cells with insertion layer usually maintain their high efficiency for weeks or even months, which exhibits the protection against the evolution of Gr/Si interface in air. However, the inhomogeneous thin insertion layers may weaken the protection effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the graphene–silicon heterostructure devices have attracted considerable recent interest. A unique feature in these devices is that the tunable work function of graphene produces a tunable barrier height across the graphene–silicon interface, which makes the graphene–silicon junction a great platform for investigating interface charge‐transport mechanisms as well as diverse device applications such as barristors, photodetectors, high‐speed modulators, solar cells, and chemical sensors . However, the studies to date are largely limited to the heterostructures formed between graphene and lightly doped silicon with a considerable Schottky barrier, and the thermionic emission is believed to dictate the carrier‐transport process.…”
mentioning
confidence: 99%
“…They concluded that large-scale CVD graphene applications might be hindered due this latter effect. Recently, Ho et al [30] demonstrated a graphene/TiOx photoactive heterostructure cathode to fabricate an (n) graphene/(p) Si Schottky junction with power conversion efficiency > 10 %. These recent advances [31] shine light on the integration of graphene in solar cell applications that are already competitive with respect to organic based demonstrators but also on field effect devices where graphene can be implemented as a channel or a floating gate [3,32].…”
Section: Introductionmentioning
confidence: 99%